Validated physical models and parameters of bulk 3C-SiC aiming for credible technology computer aided design (TCAD) simulation - Arvanitopoulos, A.; Lophitis, Neophytos; Gyftakis, K. N.; Perkins, Samuel; Antoniou, M. (My University, 2017)
The cubic form of SiC (β- or 3C-) compared to the hexagonal α-SiC polytypes, primarily 4H- and 6H-SiC, has lower growth cost and can be grown heteroepitaxially in large area silicon (Si) wafers which makes it of special interest. This in conjunction with the recently reported growth of improved quality 3C-SiC, make the development of devices an imminent objective. However, the readiness of models that accurately predict the material characteristics, properties and performance is an imperative requirement for attaining the design and optimization of functional devices. The purpose of this study is to provide and validate a comprehensive set of models alongside with their parameters for bulk 3C-SiC. The validation process revealed that the proposed models are in a very good agreement to experimental data and confidence ranges were identified. This is the first piece of work achieving that for 3C-SiC. Considerably, it constitutes the necessary step for finite element method simulations and technology computer aided design.
Keywords: silicon carbide; technology computer aided design (TCAD); wide bandgap